Comparative proteomic profiling of H. pylori induced Gastric Cancer Serum with healthy serum samples (International Journal of Food and Nutritional Sciences, 2022)
Gastric Cancer (GC) is the third most common cause of death from cancer, accounting for about 7,83,000 deaths in males and females throughout the world. Therewere very few studies has been made on population specific biomarker studies withrespect to Helicobacter pylori (H. pylori) induced gastric cancer in India. Hence, the present study aimed toexecute this biomarker study involving positive and negative healthy serumsamples of H. pylori in comparison with H. pylori positive gastric cancer samples.